Zinc/iron-regulated transporter-like protein gene family in Theobroma cacao L: Characteristics, evolution, function and 3D structure analysis - Pacheco, Daniel Dastan Rezabala; Santana, Brenda Conceição Guimaraes; Pirovani, Carlos Priminho; de Almeida, Alex-Alan Furtado (Frontiers in Plant Science, 2023)
The Zinc/Iron-Regulated Transporter-Like Protein (ZIP) gene family first identified in plants is highly distributed in the plant kingdom. This family has previously been reported to transport several essential and non-essential cationic elements, including those toxic to many economically important crops such as cacao (Theobroma cacao L.). In this study, 11 non-redundant ZIP genes in cacao distributed in five chromosomes were characterized based on their physicochemical properties, evolution, duplication, gene structure, promoter region, three-dimensional protein structure and protein-protein interaction. The 11 TcZIP genes were predicted to encode proteins from 309 to 435 aa, with localization in the plasma membrane and chloroplast containing 6-9 putative domains (TM). Interspecies phylogenetic analysis subdivided the ZIP proteins into four groups. Segmental duplication events significantly contributed to the expansion of TcZIP genes, these genes underwent high pressure of purifying selection. The three-dimensional structure of the proteins showed that the α helix conformations are predominant with several pocket sites, containing the metal binding site, being the residues leucine (LEU) alanine (ALA), glycine (GLY), serine (SER), lysine (LYS) and histidine (HIS) as the most predicted. Regarding the analysis of protein-protein interaction and enrichment of the gene ontology, four biological processes were attributed as DNA metabolic process, cation transport, transcription regulation and regulation of macromolecule biosynthetic process and negative regulation of plant-type hypersensitive response and negative regulation of innate immune response. Additionally, our discovery expand knowledge about the function, evolution, protein structures and interaction of ZIP family proteins in T. cacao, as well as information to develop cacao genotypes enriched with important mineral nutrients as well as genotypes that bioaccumulate or exclude toxic metals.